The Peacemaker’s poison pill: Jus cogens and the Dayton Accords - Muhammad Dwistaraifa Rasendriya (Institute Of computer Science (IOCS), 2026)
The rigid invalidating effect of jus cogens on a conflicting peace treaty may risk blocking a pathway to peace. This article tests this tension through a case study of the 1995 Dayton Peace Agreement, employing a doctrinal analysis of treaties, case-law, and international materials. It contrasts textual and functional interpretations under the Vienna Convention on the Law of Treaties. The analysis finds that while Dayton is textually valid for ending atrocity, it functionally conflicts with jus cogens by entrenching territories born of ethnic cleansing. It concludes that the international community’s endorsement has tempered this conflict for the sake of stability, but it also proposes a legal compromise: partial invalidity of entrenching clauses paired with positive obligations for restitution and minority return. This ensures peace is disciplined, preventing a violation of fundamental norms, and a return to armed conflict.